Engineered cylindrical NiFe magnetic nanoparticles for cancer cell death - Wong, Shawn De Wei (2019)
This thesis investigates the magnetization dynamics of cylindrical NiFe magnetic nanoparticles (MNPs), fabricated by template-assisted pulsed electrodeposition and differential chemical etching technique. Upon relaxation from a magnetically saturated state, a double vortex nucleation consisting of a clockwise and an anticlockwise vortex forms at the opposite ends of the MNP, which gradually extends and is connected via a third vortex core on its curved surface. Micromagnetic simulations revealed that the magnetization reversal occurs via the nucleation of the triple vortex state and abrupt splitting of the clockwise and anticlockwise vortices. The application of different magnetic field configurations to control the MNPs can manipulate the pathways leading to cell death, playing a pivotal role in cancer treatment. In an alternating magnetic field, the magnetic hysteresis of the MNPs results in heat dissipation that causes necrosis of cancer cells. High aspect ratios MNPs were observed to form the triple vortex state, which displayed high heating efficiency as measured by the specific absorption rate. For uniform magnetic fields, biaxial field configuration has been shown to be the most efficient magneto-actuated cell apoptosis method, which maximized the induced magnetic torque. Light transmissivity dynamics showed that MNPs under the biaxial field configuration have higher responsiveness over a wide range of frequencies as compared to uniaxial field configurations. The magneto-mechanical cell destruction efficacy was substantiated by a greater reduction in cell viability in in vitro experiments. High aspect ratios MNPs with the triple vortex state had increased low field susceptibility that translated to a larger magneto-mechanical actuated force, leading to higher efficacy in cell death. For non-uniform magnetic fields, MNPs in a strong vertical magnetic field gradient were able to apply sufficient force on the cell to trigger the intracellular pathway for cell apoptosis, thus significantly reducing cell viability. In contrast, MNPs in an alternating magnetic field gradient can effectively rupture the cell membrane leading to higher lactate dehydrogenase leakage and lower cell viability, proving to be an effective induction of cell death via necrosis. The capability of the MNPs as both magnetic hyperthermia and magneto-actuation cell destruction agents is demonstrated by inducing different cell death signaling pathways, exemplifying the intricate interplay between apoptosis and necrosis.